Cloud Computing and Security : First International Conference, ICCCS 2015, Nanjing, China, August 13-15, 2015. Revised Selected Papers - Huang, Zhiqiu; Sun, Xingming; Luo, Junzhou; Wang, Jian.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the International Conference on Cloud Computing and Security (ICCCS 2015) will be held on August 13-15, 2015 in Nanjing, China. The objective of ICCCS 2015 is to provide a forum for researchers, academicians, engineers, industrial professionals, students and government officials involved in the general areas of information security and cloud computing.
Data Security -- System Security -- Cloud Platform -- and Data Analysis in Cloud.
Keywords: Computer Communication Networks; Computer software; Information Systems; Data encryption (Computer science).; Computer science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Cryptology; Computers and Society